Cooling characteristics of warm mix asphalt for multi-lift pavement repair and resurfacing. Issue 9 (29th July 2021) - Zhu, B.; Chu, L.; Fwa, T. F.
ABSTRACT: Warm mix asphalt is gaining increasing acceptance in pavement construction due to their advantages in energy saving, reduced emissions and improved worker comfort. This paper highlights another benefit of warm mix asphalt (WMA) in allowing shorter road closure time window for pavement repair or resurfacing works as compared with the conventional hot mix asphalt (HMA) construction. This is of good practical value to busy roads where closure time windows as short as 4–5 h are common. A finite-element simulation model for predicting temperature cooling of WMA and HMA was developed to study the potential benefits of WMA in allowing shorter time windows for pavement repairs and resurfacing operations. Full-scale field trials were conducted to compare the temperature cooling characteristics of multi-lift construction of WMA and HMA, and provide the necessary data to calibrate and validate the simulation model developed. The validated simulation model was employed to analyse the cooling characteristics of HMA and WMA resurfacings under different environmental conditions and resurfaced layer thicknesses. These analyses provide useful information on the length of cooling time needed before the resurfaced layer is sufficiently stable to receive traffic. It was found that, compared with HMA, the use of WMA shortened the night-time cooling time needed by 5–35 min when the resurfacing thickness increased from 75 to 150 mm. The corresponding cooling time reductions for day-time paving were 19–79 min.